Experiential Marketing and Quality Drive Coffee Shop Loyalty in Indonesia: Pemasaran Eksperiensial dan Kualitas Mendorong Loyalitas Kedai Kopi di Indonesia - Kushenda, Dimas Ardyadheva; Hariasi, Misti (Universitas Muhammadiyah Sidoarjo, 2024)
This study analyzes the effects of Experiential Marketing, Product Quality, and Service Quality on consumer loyalty at a coffee shop in Pandaan. Using an associative quantitative approach, data from 100 consumers were collected via questionnaires and processed with SPSS. Results indicate that all three factors positively and significantly impact consumer loyalty. These findings suggest that improving these aspects can enhance customer loyalty. The study fills a knowledge gap by providing empirical evidence on the importance of experiential marketing, product quality, and service quality in the coffee shop industry. Highlight: Experiential Marketing positively impacts consumer loyalty. High product quality boosts customer retention. Excellent service quality enhances repeat purchases. Keywoard: Experiential Marketing, Product Quality, Service Quality, Consumer Loyalty, Coffee Shop